Penerapan Pembelajaran Tematik Integratif Berbasis Kontekstual dalam Meningkatkan Keterampilan Sosial Siswa Madrasah Ibtidaiyah - Purwanti, Eri; Maisaroh, Iis; Jannah, Miftahul (Kartika: Jurnal Studi Keislaman, 2024)
This study focuses on the problem of improving students' social skills in Madrasah Ibtidaiyah (MI) through the implementation of contextual-based integrative thematic learning. This study uses a classroom action research (CAR) method with two cycles. The study results indicate contextual-based integrative thematic learning can significantly improve students' social skills. In the first cycle, there was an increase in students' social skills in only one indicator of social skills: the ability to collaborate in solving contextual problems. In the second cycle, students' social skills increased to 3 indicators, with the most visible development of communication skills in real situations and empathy in social interactions. The supporting factors for this success are the active involvement of students in contextual learning activities, the relevance of the material to everyday life, and teacher support in providing guidance and feedback. At the same time, the inhibiting factors include limited learning media and differences in students' levels of understanding. This study concludes contextual-based integrative thematic learning improves students' social skills in Madrasah Ibtidaiyah. The results of this study are expected to be a reference for teachers in implementing contextual and integrative learning to optimize the development of students' social skills.